Beyond structural motifs: the frontier of actinide-containing metal–organic frameworks. Issue 21 (18th May 2021) - Martin, Corey R.; Leith, Gabrielle A.; Shustova, Natalia B.
Abstract : This perspective deviates from exclusively focusing on structural features of actinide-containing metal-organic frameworks and pivots towards their prospect as avant-garde materials with an emphasis on their physicochemical properties. Abstract : In this perspective, we feature recent advances in the field of actinide-containing metal–organic frameworks (An-MOFs) with a main focus on their electronic, catalytic, photophysical, and sorption properties. This discussion deviates from a strictly crystallographic analysis of An-MOFs, reported in several reviews, or synthesis of novel structural motifs, and instead delves into the remarkable potential of An-MOFs for evolving the nuclear waste administration sector. Currently, the An-MOF field is dominated by thorium- and uranium-containing structures, with only a few reports on transuranic frameworks. However, some of the reported properties in the field of An-MOFs foreshadow potential implementation of these materials and are the main focus of this report. Thus, this perspective intends to provide a glimpse into the challenges, triumphs, and future directions of An-MOFs in sectors ranging from the traditional realm of gas sorption and separation to recently emerging areas such as electronics and photophysics.